Relationship Between Andragogy Trainer Competencies With the Motivation to Learn Training Participants Third Public Speaking Padang - Rika Novitri; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by the low learning motivation of the Haus Public Speaking training participants in Padang City, this is presumably because it has something to do with the andragogical competence of the Trainer in the Haus Public speaking Training in Padang City. This study aims to see an overview of the andragogical competence of the trainer, the description of learning motivation, and the relationship between the andragogical competence of the trainer and the learning motivation of the participants in the Haus Public Speaking training in Padang City. The approach to this research is quantitative with descriptive correlational research. The population in this study was 25 participants in the Haus Public Speaking training in Padang City and a sample of 70%, namely 17 people. The sampling technique was random sampling. In this study, data collection using a questionnaire or questionnaire with the data collection tool in the form of a questionnaire guide. The data analysis technique in this study used a percentage formula and rank-order correlation. The results of this study indicate that the andragogical competence of the trainer is quite low, the learning motivation of the participants is still low, and there is a significant relationship between the andragogical competence of the trainer and the learning motivation of the public speaking training participants. Suggestions are to the managers of the public speaking training program to further improve the quality of learning in public speaking training. To trainers, so they can improve their competence as educators, especially andragogical competence in public speaking training. It is hoped that in other studies, we can see some other factors that have not been examined in this study.Keywords: Andragogical Competence, Learning Motivation